Rozner, Sarah (audio interview #5 of 20) - Rozner, Sarah (b. 1892 - d. 12/?/1980); Berger Gluck, Sherna, interviewer
INTERVIEW DESCRIPTION - This is the thirteenth interview with Sarah Rozner, conducted in her home. In the beginning of the interview, it was obvious that Rozner was not feeling well. She had some problems with her speech and was not able to concentrate very well; however, by the end of the interview she seemed to be feeling better. Although the interview shifted between several topics, it generally followed a chronological sequence. TOPICS - Los Angeles laundry workers strike, 1939; struggle between AFL and the CIO; attitudes toward leaders in the union; power struggles in the union and shop;power struggles in the union in Los Angeles; role and programs she instituted at Louart; decision to retire; 10/23/1973